How Outward Bound co‐instructor relationships create a context for emotional support during stressful course situations. Issue 6 (5th April 2021) - McGovern, Gina
Abstract: Youth program leaders may experience considerable stress when they encounter emotionally demanding situations in their work. This stress can negatively affect their well‐being or interfere with their ability to provide meaningful experiences for youth. Using Outward Bound (OB) youth expedition courses as a context, this study examined how co‐instructors provided emotional support to instructors during stressful situations. Qualitative analysis of 31 OB instructor interviews showed co‐instructors used three strategies: allowing instructors to momentarily exit the situation, validating instructors' emotions, and reframing negative situations. In addition, certain relationship factors facilitated the provision of support: building holistic relationships, establishing open communication patterns, and conveying commitment. The findings suggest that these factors increased instructors' perception of support availability, which facilitated them receiving support. This study makes a strong case for the value of co‐worker relationships as a source of support for individuals in occupations where they experience emotionally stressful work situations.